3PC-070 Evaluation of compatibility of acetylsalicylic acid and atenolol with medications commonly used in intensive care units. (14th March 2021) - Lombard, A; Vigneron, J; D'huart, E; Demore, B
Abstract : Background and importance: Patients hospitalised in intensive care units (ICUs) often require the use of multiple drugs, and the intravenous (IV) route is the most common mode of administration. IV access is usually limited, leading to concomitant administration of different drugs in the same infusion line. A previous work 1 identified many administrations via a Y site without compatibility data. A list of missing data was established. Aim and objectives: From this list, we decided to evaluate the physical compatibility of two drugs frequently administered (acetylsalicylic acid and atenolol) with other drug used in ICUs by visual tests, subvisual tests and pH measurement. Material and methods: Each pair of drugs was mixed in three ratios (drug A/drug B: 9/1; 5/5; 1/9). Visual analysis, such as precipitation formation, colour change, gas formation, subvisual evaluation by UV spectrophotometry at 350, 410 and 550 nm, and pH measurements were performed for each mixture. Results: A total of 17 pairs of two drugs were tested: 10 mixtures with acetylsalicylic acid and seven mixtures with atenolol. For the mixtures with acetylsalicylic acid, eight were compatible pairs and two were incompatible pairs: acetylsalicylic acid with canreonate potassium (precipitate formation) and with Nutryelt (colouring in pink). For the mixtures with atenolol, five were compatible pairs and two were incompatible pairs: atenolol with mycophenolate (appearance of haze) and with Nutryelt (colour change). Conclusion and relevance: After laboratory tests, new incompatibilities were found which gives additional information to the literature. This study demonstrated that all mixtures were compatible except for acetylsalicylic acid with canreonate potassium and Nutryelt, and atenolol with mycophenolate and Nutryelt. However, many other mixtures should be studied due to missing data. References and/or acknowledgements: D'Huart, et al . Pharm Technol Hosp Pharm 2019;4 :29–40. Conflict of interest: No conflict of interest